Representation of Gender Injustice in Wigati Novel: A Critical Discourse Analysis of Sara Mills - Amelia, Dinda; Suryaman, Maman; Effendi, Anwar; Hartono, Hartono (Journal of Pragmatics Research, 2025)
This study aimed to analyze the representation of gender injustice in the novel Wigati by Khilma Anis in using a critical discourse analysis (CDA) approach based on Sara Mills’ theory. The study employed Sara Mills’ subject position theory to reveal how the narrative in the novel represented the positions of women and men within a patriarchal social structure. Using a descriptive qualitative method, data were collected from narrative texts that reflected gender relations, especially involving the main character and the relationship between Wigati’s mother and her father. The types of gender injustice identified included stereotyping, marginalization, subordination, and verbal or nonphysical violence. The results showed that female characters, particularly Wigati and her mother, occupied subordinate positions both socially and economically. The novel’s narrative illustrated that Wigati’s mother was forced to accept a marginalized role due to her siri marriage, which highlighted the neglect of women’s rights in a patriarchal society. The analysis also revealed that the perspectives of the narrator and other characters influenced how readers perceived gender injustice by reinforcing certain stereotypes about gender roles. Sara Mills’ theory helped in identifying how power structures and male dominance operated through narrative and reinforced gender injustice. This research aimed to contribute to a deeper understanding of how literature functions as a reflection and critique of social injustice, particularly gender-based inequality, and how it reveals the marginalized position of women within patriarchal culture.